Sleep Disorders and Their Association with Psychiatric Disorders (CIPEEX, 2025)
Introduction: This study is an integrative review of the literature on sleep disorders and their associated symptoms in relation to psychiatric disorders. Patients with sleep disorders often have comorbidities with these disorders without a direct causal relationship.  Additionally, evidence suggests that the pandemic has worsened sleep quality in children, consequently affecting their mental health. Understanding this relationship and possible intervention strategies is essential. Objectives: 1) Analyze the association between sleep disorders and psychiatric disorders. 2) Analyze possible interventions. Methodology: This integrative literature review investigated the association between sleep disorders and psychiatric disorders. To this end, searches were conducted in the Virtual Health Library (VHL) database using the following health science descriptors: "Mental Disorders," "Sleep Disorders," and "Health." After screening, five original articles published between 2020 and 2025 were included. Results: Children and adolescents with ADHD often experience sleep problems, which can exacerbate their symptoms, prompting them to seek clinical care. These sleep issues can negatively impact the quality of life for patients and their families. Children with neurodevelopmental disorders (such as ASD and ADHD) have a higher prevalence of sleep disorders than the general pediatric population. These disorders include difficulty falling asleep, nighttime awakenings, daytime sleepiness, circadian rhythm disturbances, and respiratory problems. These disorders can cause behavioral, emotional, and cognitive problems that impair academic performance and are associated with deficits in executive functions and memory. Evidence suggests that confinement during the pandemic was associated with an increase in sleep disorders related to excessive electronic device use and resistance to sleep. A study of Mexican children demonstrated this, reinforcing the role of external factors in children's mental health. The prevalence of sleep disorders is higher among adolescents with childhood anxiety emotional disorder (CAED). Loneliness, suicidal ideation, absence of physical education classes, and physical inactivity are significantly associated with CAED. Consequently, adolescents with anxiety directed at specific situations often have difficulty sleeping at night. Among adults, chronic diseases and multimorbidities were strongly associated with sleep problems. Depression and other mental illnesses were as significant as physical illnesses, such as spinal problems, lung problems, diabetes, and kidney failure, in causing sleep problems. Individuals with one or two diseases experienced approximately twice the number of sleep problems compared to those without these conditions, while individuals with three or more morbidities experienced approximately four times the number of sleep problems. Conclusions: Sleep disorders are associated with psychiatric disorders in various ways. They can be a cause or a symptom of an existing disorder. It is important to recognize that they often coexist and exacerbate each other. Early identification and treatment are crucial for a favorable prognosis and to prevent further deterioration. Tailoring specific interventions for each disorder to the uniqueness of each case is important to promote functional outcomes and respect patient subjectivity. Additionally, gender differences and vulnerabilities should be considered, as studies indicate significant variations in outcomes between men and women, as well as between more vulnerable groups.
Keywords: Mental disorders; sleep disorders; Health